Socioeconomic determinants of the professionalization of Shuar indigenous women in Ecuador (Praxis Educativa, 2026)
The professionalization of Shuar Indigenous women represents both a challenge and a key opportunity to promote equitable development in Ecuador. Although progress has been made in access to education, structural and sociocultural barriers still hinder their full integration into academic and professional spheres. This study aimed to analyze the socioeconomic factors that influence this process. A quantitative, non-experimental, explanatory, and cross-sectional approach was used, with stratified sampling applied to a population of 2,051 women. Statistical analyses revealed significant associations between skills development and factors such as the institutional environment, sociocultural barriers and support, as well as training and opportunities. The study concludes that strengthening intercultural scholarships, implementing inclusive policies, and consolidating community networks are essential to promoting the professionalization of Shuar women and overcoming cultural and economic barriers.
Keywords: Indigenous women, professionalization, socioeconomic factors, education, interculturality